The stuffed bear mystery - Warner, Gertrude Chandler, 1890-1979.; Soileau, Hodges (New York : Scholastic, 2002)
The Boxcar children, while participating in the "Teddy bear festival," help recover a valuable teddy bear that disappeared from the toy hospital.
Keywords: Teddy bears -- Juvenile fiction; Bears -- Juvenile fiction; Soft toys -- Juvenile fiction; Orphans -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Mystery fiction